The intelligent fault diagnosis frameworks based on fuzzy integral - Karaköse, M.; Aydin, I.; Akin, E. (My University, 2010)
Fuzzy integral is an information aggregation and combination process in a multi-criteria environment using fuzzy measures. This paper presents a new data fusion method using fuzzy integral for fault diagnosis. The method consists of two frameworks. The first framework was employed to identify the relations between features and a specified fault. The second framework was implemented to integrate different diagnosis algorithms to improve the accuracy rates of them. The choquet fuzzy integral was utilized for two frameworks. The proposed approach was experimentally implemented on a 0.37 kW induction motor. Broken rotor bar and stator faults were evaluated to validate the models. The results showed that the proposed method performs very well for broken rotor bar and stator faults. © 2010 IEEE.
2010 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2010 -- 14 June 2010 through 16 June 2010 -- Pisa -- 81684
Keywords: Fault diagnosis; Fuzzy integral; Induction motors; Intelligent techniques; Signal processing